Interaction of an Elevated Low Velocity Ratio Turbulent Jet with Atmospheric Crossflow: An IDDES Study - Yilmaz, Ilyas (Springer International Publishing Ag, 2024)
Improved Delayed Detached Eddy Simulation (IDDES) of an elevated low velocity ratio turbulent round jet in atmospheric crossflow is presented. Atmospheric inlet boundary condition is specified at inlet. A commercial CFD software SimFlow, which is based on the open source numerical framework OpenFOAM, is used to generate grid and numerically solve the governing equations. It was found that the flow field is characterized by simultaneous formation and strong interaction of two separate wake regions, leading to a very complex and highly unsteady vortical flow patterns which show unstable, transitional behavior. The results also show that the IDDES is fairly capable of identifying the near-field wake region unsteady flow characteristics and large scale coherent flow structures such as a horse-shoe vortex, shear layer vortices, trailing vortices, separation and recirculation zones, a counter-rotating vortex pair, hairpin (Omega-shape) vortices and the Kelvin-Helmholtz roll-ups, as described in the corresponding literature. Formation of the von Karman vortices and their shedding characteristics in time are also captured.
14th International Conference on Computational Heat and Mass Transfer (ICCHMT) -- SEP 04-08, 2023 -- Dusseldorf, GERMANY
Keywords: Low Velocity Ratio Jet; Elevated Jet; Atmospheric Crossflow; Iddes